Righteous prey [compact disc, unabridged] - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Virgil Flowers., 2022)
'We're going to murder people who need to be murdered.' So begins a press release from a mysterious group known only as 'The Five,' shortly after a vicious predator is murdered in San Francisco. The Five is believed to be made up of vigilante killers who are very bored, and very rich. They target the worst of society, rapists, murderers, and thieves, and then use their unlimited resources to offset the damage done by those who they've killed, donating untraceable Bitcoin to charities and victims via the dark net. The Five soon become the most popular figures on social media, a modern-day Batman, though their motives may not be entirely pure. After a woman is murdered in the Twin Cities, Virgil Flowers and Lucas Davenport are sent in to investigate. And they soon have their hands full, the killings are smart and carefully choreographed, and with no apparent direct connection to the victims, The Five are virtually untraceable. But if anyone can destroy this group, it will be the dynamic team of Davenport and Flowers.